Patchouli Oil Isolation and Identification of Chemical Components Using GC-MS - Souhoka, Fensia Analda; Al Aziz, Andi Zulkifli; Nazudin, Nazudin (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
This research aims to isolate oil from patchouli (Pogostemon cablin Benth) and identify the chemical components of patchouli oil using Gas Chromatography-Mass Spectrometry (GC-MS). Patchouli plant samples were obtained from Welulu Village, Kolaka Regency, Southeast Sulawesi Province. Fresh patchouli leaves are dried in the sun for four days to a constant weight. Patchouli leaves water content is 77.41% (w/w). Dry patchouli leaves are distilled using the water and steam method for two hours. Water and oil distillates are separated using a separating funnel. Patchouli oil obtained was dried using Na2SO4 anhydrous and yield 0.73% (w/w). The results of GC-MS analysis showed that patchouli oil contained 13 chemical components compounds, namely Î²-patchoulene (4.56%), cedr-8-ene (1.24%), trans-caryophyllene (7.96%), Î±-guaiene (18.61%), seychellene (5.70%), patchoulene (2.88%), eremophilene (1.33%), azulene (8.74%), delta-guaiene (18.90%), cyclohexanone (1.10%), globulol (1.88%), veridiflorol (4.39%), and alcohol patchouli (22.7%).